COMMUNICATION DYNAMICS THROUGH INSTANT MESSAGING APPLICATIONS: A LITERATURE ANALYSIS OF THE TELEGRAM AND WHATSAPP PLATFORMS - Indah Sulistiani; Al-Amin (Adisam Publisher, 2025)
This research analyses the dynamics of communication through instant messaging applications, with a particular focus on two popular platforms, Telegram and WhatsApp. Through a comprehensive literature review, it is found that Telegram and WhatsApp have unique characteristics that influence users' communication patterns. Telegram is known for its flexibility in managing large groups and advanced feature integration, while WhatsApp is recognised for its strong end-to-end encryption and user-friendly interface. These differences make the choice between the two platforms dependent on specific usage needs-Telegram is more suitable for complex group communications, while WhatsApp is ideal for personalised interactions with a high priority on privacy. The conclusions of this study help in understanding the advantages and disadvantages of each app and provide guidance in choosing the right communication platform according to user needs.